Relationship between psycho-demographic factors and civil servants’ attitude to corruption in Osun State, Nigeria (2010)
The relationship between psycho-demographic factors and attitude to corruption (ATC) was investigated. The cross-sectional survey included 600 local government civil servants following multi-stage sampling. A 58-item self report validated questionnaire was used for data gathering. There was significant relationship between; personality (r = 0.543, P<.05), fraudulent intent (r = 0.557, P<.05), N-Ach (r = 0.476, P<.05) and ATC. Fear of crime (r = -.449, P<.05) had an inverse relationship with ATC. Personality was the most potent predictor of ATC (β = 0.251, t = 5.645, P <.05). There was significant relationship between age (r=.203, P<.05) and ATC. This study provides insight to the role of these psychological factors and age as fundamental to improving public servants’ ATC, especially in Nigeria. Utilisation of these findings will also be useful in staff recruitment and reduction of corruption in private and public administration in other settings